The Impacts of Justification of Income Inequality on the Confidence in the Women’s Movements: Empirical Evidence From Asia-Pacific Countries - Byung-Deuk Woo; Jeongho Choi (SAGE Open)
How is economic inequality associated with gender inequality at the individual level? Even though previous literature has broadened our understanding of the impacts of economic inequality at the national level, the influence of attitudes toward income inequality on the attitudes toward gender equality has not been fully examined at the individual level. To contribute to the previous literature, relying on the World Value Survey dataset in Wave 5, 6, and 7, this article unveils the relationship between economic inequality and gender inequality at the individual level with the cases of 17 Asia-Pacific countries. Estimating ordered logistic regression models, this article demonstrates that there is a statistically and substantially significant relationship between the justification of income inequality on the confidence in the women’s movements. More interestingly, we find that male respondents compared to their female counterparts are more susceptible to the changes in the justification of income inequality. Our research advances the literature on the impacts of economic inequality concerning individual perspectives. At the same time, this article extends previous research on the influence of economic inequality by showing that the role of economic inequality in determining people’s attitudes toward gender equality is conditioned by the gender of individuals.